Dissimilar Resistance Spot Welding of Q&P and TWIP Steel Sheets. Issue 3 (17th February 2016) - Russo Spena, Pasquale; De Maddis, Manuela; Lombardi, Franco; Rossini, Matteo
Abstract : Dissimilar resistance spot welding of twinning induced plasticity (TWIP) and quenching and partitioning (Q&P) steel grades has been investigated by evaluating the effects of clamping force, welding current, and welding time on the microstructure, shear tension strength, and fracture of welded samples. The spot welding of TWIP and Q&P steels promotes the occurrence of an asymmetrical weld nugget with a greater dilution of TWIP steel because of its lower melting temperature and thermal conductivity. As a result, weld nuggets exhibit an austenitic microstructure. TWIP steel undergoes a grain coarsening in the HAZ, whereas Q&P steel undergoes some phase transformations. Welded samples tend to exhibit higher shear tension strength as they are joined at the highest welding current, even though an improper clamping force can promote excessive metal expulsion, thereby reducing the mechanical strength of the welded joints. Shear tension welded samples failed through interfacial fracture with partial thickness fracture mode for a low welding current, while partial thickness with button pull fractures were observed when a high welding current was used. The weld spots predominantly failed at the TWIP side. However, as TWIP steel can work harden significantly in the more resistant welded joints, the failures occur, instead, at the Q&P side.